Sensitivity and Working Range of Backside Calibration Potentiometry - Ngeontae, W.; Xu, Y.; Xu, C.; Aeungmaitrepirom, W.; Tuntulani, T.; Pretsch, E.; Bakker, Eric (American Chemical Society, 2007)
A new direction in potentiometric sensing, termed backside calibration potentiometry, was recently introduced. It makes use of the fact that the stir effect disappears in the absence of an ion-ionophore complex concentration gradient across supported liquid ion-selective membranes. This method is especially suitable for measurements in which recalibration in the sample is not feasible, such as in remote monitoring applications. Here, a theoretical model is established to predict the workingconcentration range of the method. Lead(II)-selective Celgard membranes were used here with H+ as the dominant interfering ions. The emf difference for stirred and unstirred solutions was measured, and the magnitude of this emf change as a function of the sample Pb2+ concentration was found to exhibit a bell shape that spans ~3 orders of magnitude. The concentration of interfering ions and the selectivity of the membrane were demonstrated to be important factors that affect the working range. Smaller ratios of primary ion concentrations at both aqueous sides of the membrane gave smaller emf differencevalues, and emf changes could still be observed with a logarithmic concentration ratio of 0.05. All experimental results correlated satisfactorily with the theoretical model.